Role of Isospin Momentum Dependent Interactions in Multifragmentation of Mass Asymmetric Colliding Nuclei - Kaur, Ramandeep (My University, 2014)
The main motive of the present thesis is to investigate the contribution of isospin momentum dependent interactions in the multifragmentation of asymmetric colliding nuclei, in which the mass of target nuclei is fixed and the mass of projectile nuclei is varied. These different combinations of projectile and target nuclei have been simulated within the framework of Isospin Quantum Molecular Dynamics model (IQMD) and IQMD (Th01) model for the respective momentum dependent and isospin momentum dependent interactions. The results clearly signifies the importance of isospin momentum dependent interactions for asymmetric colliding pairs. Thus, the isospin dependence of momentum dependent interactions should be taken into account for the various studies related to highly asymmetric reactions.
MS, SPMS
Keywords: Fragments; Single ratio; Correlations; IQMD model; Relative momentum